'Expect the Worst': Modern Life and Sentimental Death in Just Around the Corner (Marion 1921). (11th November 2017) - Brouwers, Anke
Abstract: The silent film adaptation of Hurst's Just Around The Corner (1921) by writer-director Frances Marion foregrounds three themes that also feature centrally in the short story: the hardship and struggles of modern work, the difficulties and exigencies of modern love, and the symbolically transformative powers of death. Both film and story negotiate the stylistic, social, economic and cultural contradictions and compromises of American society and Hollywood on the cusp of change. Marion's dramatization explicitly brings to fore the tensions between progressive and conservative attitudes towards modernity and stages the conflicting morals of the times from a gendered perspective. As a result, Just Around the Corner is both formally and thematically an example of the challenging dialogue between progressive, proto-feminist attitudes developing in the late teens and early twenties (and intrinsic to female artistic practice) and the old-fashioned morality of conservative discourses and the narrative conventions of mainstream Hollywood filmmaking.